Study on the Contact Stress Distribution Model of Asphalt Mixture Particles. (12th September 2022) - Wang, Lei; Yang, Xiucheng
Abstract : The distribution of contact stress of particles in asphalt mixture could be used to reflect the relationship between the macroscopic mechanical properties and the mesostructure of the material. However, there is no mature method to obtain the internal stress characteristics of asphalt mixture. In this study, the accurate stress distribution and stress transfer state information of particles in asphalt mixture were obtained by using pressure film technology, which provided a good theoretical basis for material gradation design. The pressure film was sandwiched between two Marshall specimens, and the compression part will appear red. After digital processing by software, the total contact area and stress distribution of the two specimens can be obtained. Three kinds of asphalt, three kinds of asphalt pavement gradation, and five kinds of asphalt aggregate ratio were selected to prepare asphalt mixture specimens. The effects of different asphalt, skeleton structure, and asphalt film thickness on the contact characteristics of aggregates were studied. The test results showed that, when the pressure between the two specimens is 0.23 MPa, the contact area of the particles reaches the maximum. The relationship between the contact point distribution probability and the pressure was fitted into a nonlinear curve. The gradation of the mixture, the type of asphalt and the thickness of the asphalt film were used as parameters A, B, and C. The prediction model had a good correlation with the test results. The prediction model proposed in this study could be used to improve the experimental efficiency, save test material and financial resources, as well as get complete contact stress information of the internal particle interface of asphalt mixture.